1986
DOI: 10.1159/000124566
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Posterior Pituitary Lobectomy: Prolonged Elevation of Plasma Prolactin and Interruption of Cyclicity

Abstract: We previously reported that the posterior pituitary dopaminergic system participates in the inhibition of prolactin (PRL) secretion in both male and lactating female rats. However, posterior pituitary lobectomy (Lobex) of urethane-anesthetized cycling rats resulted in an elevation in plasma PRL for a short time only. This raises a question regarding the importance of input from the posterior pituitary to the control of PRL secretion during the estrous cycle. The objectives of this study were (1) to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…However, our results do not rule out the possibility that these peptides may also affect the activity of the THDA neurons [12, 13, 14, 15, 16, 17]and/or the activity of prolactin-releasing factors [7, 8, 9, 10], for review see 11]both of which play an important role in prolactin release during lactation. We have previously shown that while β-endorphin antiserum abolished the prolactin secretory response to suckling, it did not prevent the suckling-induced inhibition of TIDA neurons [37], indicating that this peptide has a different mechanism of action.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, our results do not rule out the possibility that these peptides may also affect the activity of the THDA neurons [12, 13, 14, 15, 16, 17]and/or the activity of prolactin-releasing factors [7, 8, 9, 10], for review see 11]both of which play an important role in prolactin release during lactation. We have previously shown that while β-endorphin antiserum abolished the prolactin secretory response to suckling, it did not prevent the suckling-induced inhibition of TIDA neurons [37], indicating that this peptide has a different mechanism of action.…”
Section: Discussionmentioning
confidence: 80%
“…While the TIDA system is considered to be a major regulator of prolactin secretion, the tuberohypophyseal dopaminergic (THDA) system, also plays an important role in the regulation of prolactin release during lactation [12, 13, 14, 15, 16, 17]. These neurons arise from the rostral portion of the arcuate nucleus and terminate in the intermediate and neural lobes of the pituitary gland [for review see 6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested, however, that IL and NL may contribute greater than 50% of the DA in the AL, presumably through the SPV [6]. Given the importance ascribed to the neurointermediate lobe in the control of the surge of PRL secreted into serum on PRO [13, 14, 15], we compared the changing concentrations of DA and DOPAC in AL, IL, and NL throughout the 4-day estrous cycle of the rat in order to gain insight into the relative contribution of each lobe to the regulation of the secretion of PRL.…”
Section: Introductionmentioning
confidence: 99%
“…It In rats, acute or chronic posterior pituitary lobectomy produces an increase in plasma prolactin [3,4,5]. On the other hand, it is well known that prolactin physiologically regulates the water and electrolyte balance in teleost fish [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies strongly suggest that the posterior pituitary plays an important role in prolactin secretion. Ben Jonathan et al [3,4,5] reported that posterior pituitary lobectomy signi- …”
Section: Introductionmentioning
confidence: 99%